There is a bird on your head! - Willems, Mo. (New York : Hyperion, 2007)
Gerald the elephant discovers that there is something worse than a bird on your head-- two birds on your head! Piggie will try to help her best friend.
Keywords: Elephants -- Juvenile fiction; Swine -- Juvenile fiction; Birds -- Juvenile fiction; Elephants -- Fiction; Swine -- Fiction; Birds -- Fiction; Pigs -- Fiction; Elephants -- Fiction; Birds -- Fiction; Cooperativeness -- Fiction; Friendship -- Fiction; High interest-low vocabulary books